How to determine Sample Size: the Design of Sample Size in Health Studies - Eldawi Ahmed, Eihab Abdel Rahim; Mahfouz, Mohamed Salih; Omer Fdul, Isam (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 2 (2011), 2011)
Sample-size determination is often an important step in planning a health study—and it is usually a difficult one. Among the important hurdles to be surpassed, one must obtain an estimate of one or more error variances, and specify an effect size of importance. This paper offers some suggestions for successful and meaningful sample-size determination. Also discussed is the possibility that a sample size may not be the main issue and that the real goal is to design a high-quality study. Finally, criticism is made of some ill-advised shortcuts relating to testing power and sample size.